Proteomic analysis confirmed that the occurrence of diabetic sarcopenia is related to autophagy and apoptosis - Wang, Tianrui; Zhang, Liang; Jiang, Yu; Zhao, Xia; Hou, Kehao; Zhang, Yingze; Yu, Ning; Xu, Kuishuai (Frontiers in Endocrinology, 2026)
ObjectiveMore and more evidence indicates that type 2 diabetes mellitus (T2DM) can cause muscle lesions and lead to the occurrence of sarcopenia. The changes in the gastrocnemius muscle of T2DM rats were investigated by using tandem mass tag (TMT) proteomics technology, with the aim of discovering biomarkers of muscle lesions induced by T2DM and clarifying their potential biological relationships.MethodsTwelve healthy male Sprague Dawley rats were randomly divided into the Control group (n=6) and the T2DM group (n=6). The experimental group was established by intraperitoneal injection of streptozotocin at a dose of 40mg/kg combined with a high-fat and high-sugar diet, to create a T2DM rat model. Six months later, the gastrocnemius muscles of the two groups of rats were selected for histological staining and proteomic analysis. Immunohistochemical staining, WB and qRT-PCR were used to verify the expression of proteins related to autophagy and apoptosis.ResultsThe results of HE staining showed that the gastrocnemius muscles of T2DM rats were atrophied, with a reduced cross-sectional area, increased cell spacing, and signs of hemorrhage and inflammatory infiltration. The immunohistochemical staining results indicated that the expression levels of proteins related to muscle atrophy (MAFbx and Ube2b) in the gastrocnemius muscles of T2DM rats were significantly increased (P < 0.001). These histological changes were consistent with the pathological and physiological manifestations of sarcopenia. The results of proteomics revealed that 273 differentially expressed proteins (DEPs, 133 upregulated and 140 downregulated) were identified in the gastrocnemius muscles of T2DM rats. KEGG enrichment analysis showed that the DEPs were involved in 94 signaling pathways, including autophagy and apoptosis. After verifying the key proteins and genes in the autophagy and apoptosis pathways, it was found that the expressions of p62, Bax and Caspase-3 in the gastrocnemius muscles of T2DM rats significantly increased, while the ratio of LC3II/I significantly decreased. These results indicate that the autophagy level in the gastrocnemius tissues of T2DM rats significantly decreased, and the cell apoptosis significantly increased.ConclusionsThis study employed proteomics techniques to conduct bioinformatics analysis of DEPs in the gastrocnemius muscles of T2DM rats, as well as to explore potential pathogenic pathways. By verifying the proteins related to the pathways of autophagy and apoptosis in cells, we have, for the first time, confirmed through proteomics data that sarcopenia caused by T2DM may be associated with decreased autophagy and increased apoptosis. These research results provide rich data and theoretical basis for the diagnosis and treatment of diabetic sarcopenia.